Study of vitamin d levels in patients with type 2 diabetes mellitus - Dr. J.V. Srujan; Dr. Surya Prakash Rao (International Journal of Medical Research and Review, 2021)
Introduction: Diabetes is defined as a disturbance in intermediary metabolism manifesting as chronic sustained hyperglycemia, primarily due to either an absolute or a relative lack of insulin. Many epidemiological studies have demonstrated an inverse relationship between vitamin D levels and diabetes mellitus. However, there is a paucity of literature regarding the levels of vitamin D in type 2 diabetes, which is common in our community. This study was taken up to shed more light on this issue.Material and methods: This was a cross-sectional study conducted at NRI Institute of Medical Sciences, Sangivalasa, Visakhapatnam district. Cases of Type 2 Diabetes Mellitus attending to the outpatient department, diagnosed as per the ADA criteria of 2011, between the ages of 31 and 75 years constituted the material for the present study.Results and conclusion: Vitamin D levels were found to be significantly lower in the study group (19.91±7.0 ng/ml) as compared to the control group (32.22±4.0 ng/ml).